Why are Filipinos killing fellow Filipinos? : we as a people have divided into two nations and become a country at war with itself - Almonte, Jose T. (Metro Manila, Philippines : Foundation for Economic Freedom, 2008)
The book when it appeared in June 2007, immediately evoked widespread attention and interest that continues until now.
Why we are what we are -- What they say -- Book Launch speeches, 16 August 2007.
Keywords: PHILIPPINES -- POLITICS AND GOVERNMENT